A complexity approach to defining urban energy systems. (December 2019) - Basu, Sumedha; S. E. Bale, Catherine; Wehnert, Timon; Topp, Kilian
Abstract: Urban energy systems have been commonly considered to be socio-technical systems within the boundaries of an urban area. However, recent literature challenges this notion in that it urges researchers to look at the wider interactions and influences of urban energy systems wherein the socio-technical sphere is expanded to political, environmental and economic realms as well. In addition to the inter-sectoral linkages, the diverse agents and multilevel governance trends of energy sustainability in the dynamic environment of cities make the urban energy landscape a complex one. There is a strong case then for establishing a new conceptualisation of urban energy systems that builds upon these contemporary understandings of such systems. We argue that the complex systems approach can be suitable for this. In this paper, we propose a pilot framework for understanding urban energy systems using complex systems theory as an integrating plane. We review the multiple streams of urban energy literature to identify the contemporary discussions and construct this framework that can serve as a common ontological understanding for the different scholarships studying urban energy systems. We conclude the paper by highlighting the ways in which the framework can serve some of the relevant communities. Highlights: Cities are increasingly being hailed as 'key sites' or 'opportunities' for energy interventions and innovations. Literature also characterise cities as heterogeneous, interconnected and integrated and embedded in local context. Both cities and energy systems have been separately considered to be complex systems. We propose such a framework that embraces, traces and maps the complexity of urban energy systems that constitute the scope, potential, constraints, linkages and interactions of the system. It develops a detailed understanding of the agents and other elements, their networks as well as the interdependent subsystems. The framework hopes to build a shared understanding and visualisation of urban energy systems across disciplines of sustainability transitions, urban energy modelling, urban policy-making and planning